Gejala Depresi Tokoh Utama dalam Novel Represi Karya Fakhrisna Amalia - Siti Maemunah (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2021)
Symptoms of Depression in the Main Character in Fakhrisna Amalia's Refresi Novel. According to Aaron Beck, the problem in this study is more focused on the main character's depressive symptoms, who analyzes his depressive symptoms through 4 depressive symptoms. The method used in this research is qualitative. The reason for using this method is that the data presentation and data analysis in this study are presented in sentences and descriptions. The data used in this study are excerpts from dialogues from primary data sources, namely the novel Represi by Fakhrisna Amalia. The secondary data sources are obtained from reference books or documents related to the research object by reading, studying, and understanding. The data collection technique used is to collect data using reading and note-taking techniques. Read the entire contents of the novel carefully, mark the essential things in the novel, describe all the data that has been obtained from the data. In collecting the data, the form of sentences containing the psychological aspects of the main character in the novel Refresi by Fakhrisna Amalia, which is described. Based on the research results conducted in the novel Represi by Fakhrisna Amalia, there are symptoms of depression experienced by the main character: emotional, cognitive, motivational, and physical symptoms.